Selective separation of geniposide and gardenia yellow from gardenia fruit by isopropanol/salt aqueous two-phase system. Issue 7 (2nd May 2016) - Zhang, Hong-Ping; Guo, Jing-Ying; Li, Ting
ABSTRACT: Gardenia yellow and geniposide were separated simultaneously by employing isopropanol-salt aqueous two-phase system. Prior to separation, enrichment of geniposide and gardenia yellow in the same phase were obtained by aqueous two-phase system containing 2.0 mL isopropanol and 1.3 g of sodium citrate at room temperature with no pH adjustment. Their separation was achieved by multistage extraction in the same system at pH 3.2. At the end of the third extraction, the bottom phase had only geniposide, and the top phase had essentially gardenia yellow. Geniposide and gardenia yellow in the opposite phases were analyzed by the spectrophotometric method and HPLC.